The effect of Se-fortified wheat in feed on concentrations of selenium and GPx and SOD in blood of laying hens - Kralik, Zlata; Lončarić, Zdenko; Kralik, Gordana; Šperanda, Marcela; Didara, Mislav; Grcevic, Manuela; Radišić, Žarko (Acta Agraria Kaposváriensis, 2014)
The aim of the study was to determine concentrations of selenium and enzymes GPx and SOD in blood of hens which were consuming feed with Se-fortified wheat. The study was conducted on 70 Tetra SL hybrid hens which were in the 40th week of production. Hens were fed with prepared mixtures for 26 days. After this period hens' blood was sampled for analysis of selenium and glutathione peroxidase (GPx) and superoxide dismutase (SOD) content. Treatments used in the study had no effect on weight of hens and egg production between examined groups (P>0.05). Selenium content in laying hens' blood of both groups was balanced and amounted for group A=0.1878 Âµg/kg and for group B=0.1877 Âµg/kg (P>0.05). The higher activity of the GPx enzyme was determined in blood of hens from experimental group B compared to group A (42935.3 U/l and 35675.5 U/l, respectively, P
Keywords: wheat; laying hens; selenium; blood; enzymes